Interactive Effects of Nitrogen Application and Irrigation on Water Use, Growth and Tuber Yield of Potato under Subsurface Drip Irrigation - Amanpreet Kaur; Kanwar Barjinder Singh; Rajeev Kumar Gupta; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Agronomy, 2022)
Potatoes are a high-value crop with a shallow root system and high fertilizer requirements. The primary emphasis in potato production is minimizing nitrogen-leaching losses from the shallow root zone through fertigation. Therefore, a field experiment was conducted for two consecutive years, 2018–2019 2019–2020 to assess the effect of nitrogen and irrigation amount and frequency on tuber yield, water balance components and water productivity of potatoes under surface and subsurface drip irrigation. The experiment was laid out in a split-plot design with three nitrogen levels (187.5 kg N ha−1 (N1), 150 kg N ha−1 (N2) and 112.5 kg N ha−1 (N3)) in main plots and six irrigation levels in the subsurface (drip lines were laid at 20 cm depth) and one surface drip in subplots. Irrigation scheduling was based on 100% of cumulative pan evaporation at an alternate (I1) and two-day interval (I2), 80% of cumulative pan evaporation at an alternate (I3) and two-day interval (I4), 60% of cumulative pan evaporation at an alternate (I5) and two-day interval (I6) and 80% of cumulative pan evaporation at alternate days with surface drip (I7). Our results showed that potato transpiration was higher in N1 and N2 compared to N3, while soil evaporation was higher in N3 over N1 and N2. Irrigation regimes I5 and I6 had lower transpiration than I1, I2, I3 and I7, while I7 had more soil evaporation than I1, I2 and I3. Leaf area index (LAI), dry matter accumulation (DMA), root mass density (RMD) and tuber yield in N1 and N2 were at par but significantly higher than N3. The LAI and DMA were statistically at par in I1, I2 and I3 but significantly higher than recommended irrigation (I7). Tuber yield was statistically at par in I1, I2, I3 and I7 but I3 and I7 saved 20% irrigation water compared to I1 and I2. On the other hand, real water productivity (WPET) under N1 and N2 were comparable in I3 and I4 but significantly higher than recommended practice (I7) as pooled evapotranspiration (ET) and soil evaporation (E) in I7 were 19.5 and 20.6 mm higher, respectively, than in I3. Among interactive treatment combinations, N1I1, N1I2, N1I3, N1I7, N2I1, N2I2 and N2I3 recorded the highest tuber yields without any significant differences among them. Treatment N2I3 saved 20% nitrogen and irrigation water compared to all other combinations. Water productivity in N1 and N2 was comparable in I3 and I4 but significantly higher than recommended practice (I7).